Antiretroviral Adherence, Elevated Viral Load, and Drug Resistance Mutations in Human Immunodeficiency Virus–infected Women Initiating Treatment in Pregnancy: A Nested Case-control Study. (16th March 2019) - Myer, Landon; Redd, Andrew D; Mukonda, Elton; Lynch, Briana A; Phillips, Tamsin K; Eisenberg, Anna; Hsiao, Nei-Yuan; Capoferri, Adam; Zerbe, Alison; Clarke, William; Lesosky, Maia; Breaud, Autumn; et al.
Abstract: Background: Elevated viral load (VL) early after antiretroviral therapy (ART) initiation appears frequently in pregnant and postpartum women living with human immunodeficiency virus; however the relative contributions of pre-ART drug resistance mutations (DRMs) vs nonadherence in the etiology of elevated VL are unknown. Methods: Within a cohort of women initiating ART during pregnancy in Cape Town, South Africa, we compared women with elevated VL after initial suppression (cases, n = 80) incidence-density matched to women who maintained suppression over time (controls, n = 87). Groups were compared on pre-ART DRMs and detection of antiretrovirals in stored plasma. Results: The prevalence of pre-ART DRMs was 10% in cases and 5% in controls (adjusted odds ratio [aOR], 1.53 [95% confidence interval CI, .4–5.9]); all mutations were to nonnucleoside reverse transcriptase inhibitors. At the time of elevated VL, 19% of cases had antiretrovirals detected in plasma, compared with 87% of controls who were suppressed at a matched time point (aOR, 131.43 [95% CI, 32.8–527.4]). Based on these findings, we estimate that <10% of all elevated VL in the cohort may be attributable to pre-ART DRMs vs >90% attributable to ART nonadherence. Conclusions: DRMs account for a small proportion of all elevated VL among women occurring in the 12 months after ART initiation during pregnancy in this setting, with nonadherence appearing to drive most episodes of elevated VL. Alongside the drive for access to more robust antiretroviral agents in resource-limited settings, there is an ongoing need for effective strategies to support ART adherence in this patient population. Abstract : Pretreatment drug resistance mutations appear to account for only a small proportion of episodes of elevated viral load (VL) in South African women initiating antiretroviral therapy (ART) in pregnancy, with ART nonadherence appearing to explain the majority of episodes of elevated VL.